2007
DOI: 10.1002/pbc.21372
|View full text |Cite
|
Sign up to set email alerts
|

Radiation and chemotherapy combination for nasopharyngeal carcinoma in children: Radiotherapy dose adaptation after chemotherapy response to minimize late effects

Abstract: The overall prognosis was not influenced by TNM status, dose of local radiotherapy delivered or response to initial chemotherapy, but EFS was better in patients with a good response to chemotherapy. The cervical local failure rate was low despite radiotherapy dose reduction in the case of a good response to neoadjuvant chemotherapy. We also propose a reduction of nasopharyngeal radiation (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0
11

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 18 publications
3
50
0
11
Order By: Relevance
“…Although there are few randomised studies in children, recent publications have reported increased response rates and disease-free survival with chemotherapy compared with historical controls [11,23,28,29]. An interesting approach aiming to limit the radiotherapy dose to the cervical lymph nodes (and, thus, contain the related toxicity) has recently been reported by the Curie Institute in Paris, where children who responded well to neoadjuvant chemotherapy (tumor volume reduction [90 %) received lower doses of radiotherapy (\50 Gy) [30].…”
Section: Discussionmentioning
confidence: 96%
“…Although there are few randomised studies in children, recent publications have reported increased response rates and disease-free survival with chemotherapy compared with historical controls [11,23,28,29]. An interesting approach aiming to limit the radiotherapy dose to the cervical lymph nodes (and, thus, contain the related toxicity) has recently been reported by the Curie Institute in Paris, where children who responded well to neoadjuvant chemotherapy (tumor volume reduction [90 %) received lower doses of radiotherapy (\50 Gy) [30].…”
Section: Discussionmentioning
confidence: 96%
“…Nasopharyngeal carcinoma (NPC) is extremely rare in children13 with overall survival between 50% and 77% 24. Combined chemoradiotherapy constitutes the treatment of choice for this malignancy, with promising results,35 which was also the case in patient A.…”
Section: Discussionmentioning
confidence: 99%
“…Nasopharyngeal carcinoma (NPC) is scarcely reported in children,13 more often of undifferentiated type, while combined chemoradiotherapy constitutes the treatment of choice for this malignancy with promising results 35. Overall survival between 50% and 77% is reported 24.…”
Section: Introductionmentioning
confidence: 99%
“…10,[13][14][15][16][17][18][19][20][21][22] The results vary between 55% and 87% for OS and 60.6% and 77% for EFS or DFS, and the median length of observation for these cohorts was between 3.5 years and 15 years. Varan et al reported 10 retrospectively analyzed patients who received the same regimen (4 cycles of docetaxel/cisplatin plus irradiation 59.4 Gy) 23 : After a median observation of 2 years, the OS rate was 90%, and the EFS rate was 70%.…”
Section: Discussionmentioning
confidence: 99%
“…Reported survival rates vary between 55% and 90% for overall survival (OS) and between 60.6% and 77% for disease-free survival (DFS) and event-free survival (EFS). 10,[12][13][14][15][16][17][18][19][20][21][22][23] From 1992 to 2002, the first prospective NPC trial by the German Society of Pediatric Oncology and Hematology (NPC-91-GPOH), in which chemotherapy, radiotherapy, and interferon beta (IFN-b) were combined, was conducted within the GPOH. After a median follow-up of 48 months, an OS rate of 95% and an EFS rate of 91% were achieved, and the level of toxicity was acceptable.…”
Section: Introductionmentioning
confidence: 99%